Latent Congruence Model to Investigate Similarity and Accuracy in Family Members' Perception: The Challenge of Cross-National and Cross-Informant Measurement (Non)Invariance - Tagliabue, Semira; Zambelli, Michela; Sorgente, Angela; Sommer, Sabrina; Hoellger, Christian; Buhl, Heike M.; Lanz, Margherita (Frontiers in Psychology, 2021)
Several methods are available to answer questions regarding similarity and accuracy, each of which has specific properties and limitations. The paper focuses on the Latent Congruence Model (LCM; Cheung, 2009), for its capacity to deal with cross-informant measurement invariance issues. Until now, no cross-national applications of LCM are present in the literature, perhaps because of the difficulty to deal with both cross-national and cross-informant measurement issues implied by those models. The paper presents a step-by-step procedure to apply LCM to dyadic cross-national research designs controlling for both cross-national and cross-informant measurement invariance. An illustrative example on parent-child support exchanges in Italy and Germany was provided. Findings help to show the different possible scenarios of partial invariance and it is provided a discussion related to how to deal with those scenarios. Future perspectives in the study of parent-child similarity and accuracy in cross-national will be discussed.